Atypical presentation of Goldenher syndrome- a rare scenario - Lath, C; Sen, S; Mondal, M; Maiti, D; Singh, R; Bose, R (Journal of College of Medical Sciences-Nepal, 2014)
In 1952 Goldenher described a case with triad of pre auricular tags, mandibular hypoplasia and ocular (epibulbar) dermoid and described the case as Goldenger Syndrome. Exact etiology of this disease is not known. Here we present a case of Goldenher syndrome in a 5 days old newborn who presented with all the classical features except ocular involvement. Gorlin et.al named this syndrome as oculoauriculovertebral dysplasia due to presence of additional vertebral anomalies .2 Exact etiology of this disease is not known. Most of the cases are sporadic, though autosomal recessive, autosomal dominant and multifactorial inheritance has also been suggested.2.Chromosomal analysis shows no abnormalities.3 In this report we presented a case of Goldenger Syndrome in a 5 days old newborn who presented with all the classical features except occular involvement. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-4, 59-62 DOI: http://dx.doi.org/10.3126/jcmsn.v9i4.10239